Accounting for quantum effects and polysilicon depletion from weak to strong inversion in a charge-based design-oriented MOSFET model. - Lallement, C. (IEEE Transactions on electron devices)
This paper presents a simple, physics-based, and continuous model for the quantum effects and polydepletion in deep-submicrometer MOSFETs with very thin gate oxide thicknesses. This analytical design-oriented MOSFET model correctly predicts inversion and depletion charges, transcapacitances, and drain current, from weak to strong inversion and from nonsaturation to saturation. One single additional parameter is used for polysilicon doping concentration, while the quantum correction does not introduce any new parameter. Comparison to experimental data of deep-submicrometer technologies is provided, showing accurate fits both for I-V and C-V data. The model offers simple relationships among effective electrical parameters and physical device parameters, providing insight into the physical phenomena. This new model thereby supports device engineering, analog circuit design practice, as well as efficient circuit simulation.